Primary Small Cell Carcinoma of the Kidney: Disease Characteristics and Treatment Outcomes - Thomas F. Monaghan; Kyle P. Michelson; Nicholas R. Suss; Christina W. Agudelo; Syed N. Rahman; Dennis J. Robins; Viktor X. Flores; Brian K. McNeil; Jeffrey P. Weiss; Andrew G. Winer (Medicines, 2021)
Background: Primary small cell carcinoma of the kidney (PSCCK) is exceedingly rare and data on disease characteristics and outcomes are sparse. This study examines a nationally-representative cancer registry to better characterize PSCCK. Methods: We queried the National Cancer Database to identify patients with histology-confirmed PSCCK from 2004 to 2015. Adjusted Cox proportional hazards regression and Kaplan–Meier analyses were employed to assess predictors of mortality and estimate median survival time, respectively. Results: A total of 110 patients were included (47:53% female:male, 77% ≥60 years of age, 86% Caucasian). Significant predictors of mortality included female sex, age 60–69 years, treatment at an Integrated Network Cancer Program, stage cM1, and lack of surgical and chemoradiotherapy treatment. Independent protective factors were high socioeconomic status and treatment at an Academic Research Program. The estimated median overall survival time was 9.31 (95% CI 7.28–10.98) months for all patients. No differences in estimated survival time were observed across individual treatment modalities among those patients who underwent treatment (p = 0.214). Conclusions: PSCCK is an aggressive malignancy with a median survival time of less than one year. Future studies that correlate clinical tumor staging with specific treatment modalities are needed to optimize and individualize management.